Spontaneously Reported Hepatic Adverse Drug Events in Korea: Multicenter Study - Kwon, Hee (The Korean Academy of Medical Sciences, 2012)
Hepatic adverse drug reactions (ADRs) to certain drugs may differ within each country, reflecting different patterns of prescription, socioeconomic status, and culture. The purpose of this study was to assess the suspected cause of hepatic ADRs using the spontaneously reported pharmacovigilance data from Korea. A total of 9,360 spontaneously reported adverse drug events (ADEs) from nine Pharmacovigilance Centers were analyzed. Risk of hepatic ADEs was assessed by calculating the reporting odds ratio (ROR). Of the 9,360 cases, 567 hepatic ADEs were reported. The most frequently prescribed drug classes inducing hepatic ADEs were anti-tuberculotics, cephalosporins, valproic acids, penicillins, quinolones, non-steroidal anti-inflammatory drugs (NSAIDs), anti-viral agents, and statins. ROR values were especially high in anti-tuberculosis drugs, systemic antifungal drugs for systemic use, anti-epileptics, propylthiouracil, and herbal medicines. Underlying diseases such as tuberculosis (6.9% vs 0.9%), pneumonia (4.9% vs 1.7%), intracranial injury including skull fracture (4.5% vs 0.9%), HIV (3.4% vs 0.4%), subarachnoid hemorrhage (2.8% vs 0.5%), and osteoporosis (2.4% vs 1.4%) were significantly more common in hepatic ADE group. In conclusion, anti-infective drugs, anti-epileptics, NSAIDs and statins are the most common suspects of the spontaneously reported hepatic ADEs, in Korea. Careful monitoring for such reactions is needed for the prescription of these drugs.